Public Knowledge and Practices Toward Sun Exposure and Use of Sun Protection in Sibu Municipal Council Area, Sarawak, Malaysia - Nay Lwin; Hlaing Thaw Dar; Soe Min Htut (Journal of Epidemiology and Public Health, 2025)
Background: Understanding the risks and benefits of sun exposure promotes overall health and well-being by encouraging safe sun practices. The study aims to assess the knowledge and practice of sun protection in the public towards the harmful effects of prolonged sun exposure.Subjects and Method: A cross-sectional study was conducted in Sibu, Sarawak, Malaysia among 302 respondents, from October to November 2023. The respondents were recruited by a convenience sampling method. Research team members interviewed the respondents by using questionnaires with the study variables were age, gender, ethnicity, education and occupations of respondence, knowledge, practice and the reasons to use sunscreen protection. The data were analyzed descriptively using frequency tables and inferential statistics with p-value.Results: More than half of the participants (56%) had average knowledge about the harmful effects of prolonged sun exposure, and 83.1% had moderate levels of sun protection practice. Most participants wore long-sleeved clothing for sun protection and practice for physical appearance, sense of vulnerability or fear, and peer pressure. The statistical results showed no significant difference in practice between different age groups, ethnic groups, education levels, or occupations, and a significant difference was found between genders.Conclusion: Targeted interventions are needed to improve sun protection practices and reduce skin damage and cancer.